Combatting Human Trafficking Through International Legal Harmonization: A U.S.–Nigeria Comparative Perspective - Oluwafunmibi Ajakaye; Adeyinka Lawal (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Human trafficking represents one of the most egregious violations of human dignity in contemporary global society, generating billions of dollars annually while exploiting millions of vulnerable individuals worldwide. This comparative study examines the effectiveness of international legal harmonization efforts in combating human trafficking through an analysis of United States and Nigerian legal frameworks, enforcement mechanisms, and policy implementations. The research investigates how these two nations, despite their different legal traditions and developmental contexts, have adapted international anti-trafficking protocols into their domestic legal systems. The study employs a comparative legal methodology, analyzing statutory frameworks, case law, enforcement statistics, and policy documents from both jurisdictions spanning the past two decades. Key international instruments examined include the United Nations Protocol to Prevent, Suppress and Punish Trafficking in Persons, the Council of Europe Convention on Action against Trafficking in Human Beings, and various bilateral agreements between the United States and Nigeria. The research evaluates the implementation of these international standards through domestic legislation such as the U.S. Trafficking Victims Protection Act and Nigeria’s Trafficking in Persons Law Enforcement and Administration Act. Findings reveal significant disparities in implementation effectiveness, with the United States demonstrating more robust enforcement mechanisms and victim protection services, while Nigeria faces challenges related to institutional capacity, corruption, and resource constraints. However, both nations have made substantial progress in legislative alignment with international standards, particularly in areas of victim identification, prosecution protocols, and international cooperation frameworks. The study identifies key areas where legal harmonization has succeeded in creating unified approaches to cross-border trafficking cases, as well as persistent gaps that continue to impede comprehensive anti-trafficking efforts. The research contributes to understanding how international legal harmonization can be optimized to address the complex, transnational nature of human trafficking. Recommendations include enhanced bilateral cooperation mechanisms, standardized victim protection protocols, improved data sharing systems, and capacity-building initiatives tailored to developing nation contexts. The study concludes that while legal harmonization provides essential foundational frameworks, effective anti-trafficking efforts require sustained political commitment, adequate resource allocation, and comprehensive addressing of root causes including poverty, corruption, and weak governance structures.